A novel mechanism for delivering nutrition: sorghum based fortified blended foods using extrusion - Padmanabhan, Natarajan (Kansas State University, 2013)
The objective of the study was to investigate extrusion as an alternative processing method and grain sorghum as a viable substitute for corn in fortified blended foods (FBFs) used in nutrition and food assistance programs around the world. In the first part of this study, sorghum-soy blend (SSB), corn-soy blend (CSB) and whole corn-soy blend (WCSB) were developed using extrusion and compared with traditional CSB13 for physico-chemical and sensory properties. After milling of extrudates, average particle size (PS) ranged between 341-447 microns, with 78-85% below 600 microns. In general, Bostwick flow rates (VB=12-23 cm/min) of rehydrated blends (11.75% solids) were within standard specifications but higher than CSB13. Descriptive sensory analysis indicated that the sorghum-based rehydrated blends were significantly less lumpy and had a more uniform texture as compared to corn-based blends and CSB13. In the second part, the impact of decortication level and process conditions was investigated with respect to sorghum-based extruded blends. Degree of gelatinization of the whole sorghum-soy blend (WSSB) and decorticated sorghum-soy blend (DSSB) extrudates ranged from 93-97%. Expansion ratio (ER=3.6-6.1) was correlated with specific mechanical energy input (SME=145-415 kJ/kg; r=0.99) and average particle size after milling (PS=336-474 microns; r= -0.75). Rehydrated blends at 20% solids concentration provided recommended energy density (0.8 kcal/g) for FBFs. Bostwick flow rates had high correlation (r = -0.91) with pasting data (final viscosity) obtained using rapid visco analyzer (RVA). Addition of oil (5.5%) prior to extrusion was also studied, and resulted in process instabilities and also lower shelf-life as determined via descriptive sensory analysis (rancid and painty attributes) and gas chromatography-mass spectroscopy (hexanal, heptenal and octanal concentrations). In conclusion, extruded sorghum-soy blends met standard specifications for energy density and consistency (Bostwick flow rate), and were superior in some aspects as compared to extruded corn-soy blends and traditional corn-soy blends (CSB13). Relationships between extrusion mechanical energy input, expansion, particle size after milling and consistency of rehydrated blends were established. Consistency of the rehydrated blends is an extremely important criterion as it affects the ease of ingestion by target consumers (children below 5 years, in this case).
Keywords: US Food Aid; Sorghum Soy Blend; Extrusion; Physicochemical Analysis; Shelf-Life Analysis; Sensory Analysis; Food Science (0359); Health Care Management (0769); Health Sciences (0566)